Digital Simulation And Intelligent Control Of CSI-Based STATCOM - Chia, Boniface Hung Kwang (2004)
A static synchronous compensator (STATCOM) is a typical FACTS ( Flexible AC Transmission System) device, which plays a significant role in reactive power compensation. This project aims to design a nonlinear multivariable control technique for Current Source Inverter(CSI)-based STATCOM in order to overcome the drawback of cascaded PI controller.